SILVER MINERALS FROM QUARTZ VEINS OF THE KRASNOE DEPOSIT (BODAYBO ORE REGION) - E.E. Palenova; I.A. Blinov; M.V. Zabotina (Минералогия)
The paper characterizes silver tellurides, sulfotellurides and sulfosalts from the quartz-galena veins of the Krasnoe deposit (Bodaybo region), which is hosted by Upper Proterozoic carbonaceous clastic rocks. Electrum (AuAg), hessite (Ag2 Te), cervelleite (Ag4 TeS), benleonardite (Ag8 (Sb,As) Te2 S3 ), unidentified silver sulfosalt, and Cd-freibergite ((Cu,Ag)10Cd2 Sb4 S13) form inclusions in galena. Sphalerite and chalcopyrite associated with galena are characterized by the presence of silver in their composition and are replaced by secondary acanthite (Ag2 S). Greenockite is closely associated with silver minerals.